Food consumption of wintering harp seals, Phoca groenlandica, in the St. Lawrence estuary, Canada - Murie, D. J.; Lavigne, D. M. (Canadian Journal of Zoology, 1991)
Diet composition and rates of food consumption were determined for 25 harp seals (Phoca groenlandica) wintering in the St. Lawrence estuary, Canada, in January and February 1983. Capelin (Mallotus villosus) was the predominant food item in stomachs (100% frequency of occurrence, 86% numerical abundance, 77% mass, 86% gross energy). Juvenile harp seals (mean mass = 64 ± 12 kg, n = 8) consumed 2.0 ± 0.6% of their total mass or 4.2 ± 1.4% of their core mass in fish daily, from which they obtained 3065 ± 1096 kcal∙d −1 . Mature harp seals (mean mass = 134 ± 28 kg, n = 17) consumed fish equivalent to 1.8 ± 1.0% of total body mass or 3.6 ± 2.1% of core body mass and acquired 5226 ± 2700 kcal∙d −1 . Food consumption did not vary with sex or maturity status when adjusted for differences in body size (analysis of covariance, P > 0.30).